A case of CADASIL caused by NOTCH3 c.512_605delinsA heterozygous mutation. Issue 11 (24th September 2021) - Liu, Jiahui; Zhang, Qiaoyu; Wang, Qi; Luan, Siyu; Dong, Xiang; Cao, Hua; Tao, Dingbo; Dong, Huijie; Ji, Xiaofei
Abstract: Background: Autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a cerebrovascular disease closely related to the NOTCH3 gene. More than 200 mutations in this gene have been reported to be associated with this disease. Methods: The NOTCH3 gene from CADASIL patient was screened for mutations by whole‐exome sequencing (WES). PCR amplification and direct Sanger sequencing were used to verify the suspicious gene mutation sites detected by WES. Results: We performed second‐generation sequencing on a sample of the patient's genome and found a heterozygous deletion‐insertion mutation c.512_605delinsA in exon 4 of NOTCH3, which resulted in amino acid changes p.G171_A202delinsE. This variation was confirmed by the direct Sanger sequencing. It may be rated as a CADASIL clinical variation. Conclusion: Discovery of this mutation site provides an important theoretical basis for specific gene‐based diagnosis and treatment of CADASIL.